Implementasi Pembelajaran Berbasis E-Learning di Masa Pademi Covid 19 dalam Meningkatkan Inovasi Guru - Eliza, Futri; Warlizasusi, Jumira (JOEAI (Journal of Education and Instruction), 2021)
This study aims to reveal how high teachers innovate in implementing e-Learning-based learning during the Covid 19 Pandemic at SMA Negeri 4 Rejang Lebong. This research is action research, namely supervisory action research. The population in this study were all teachers of class XII as many as 25 people. This action research was carried out in 2 cycles. Data collection techniques using observation techniques of e-Learning learning activities and field notes. The instrument used is an observation sheet that has been valid and reliable. Data analysis carried out is quantitative and qualitative data analysis. The implementation of academic supervision that has been carried out by researchers is able to increase teacher innovation in implementing e-Learning-based learning. The average value of teacher skills in Cycle I was 74.25 (enough category) increased to 79.5 (Good category) in Cycle II. In conclusion, the implementation of e-Learning-based learning supervision that has been carried out by researchers is able to increase teacher innovation in implementing online learning programs at SMAN 4 Rejang Lebong. Keywords: Teacher Innovation, e-Learning Learning, Academic Supervision